Milonina, alcaloide de cissampelos sympodialis EICHL. (Menispermacea) inibe inflamação aguda mediada por mastócito - Alves , Adriano Francisco (2016)
Cissampelos sympodialis Eichl (Menispermaceae) is a native plant of Paraiba region which is used in folk medicine to treat various inflammatory conditions such as asthma and rhinitis. This plant has several biologically active metabolites such as warifteine, methyl warifteine, milonine, among others. Preliminary data show that warifteine exhibits anti-inflammatory activity in a murine model of asthma. The aim of this study was to evaluate whether milonina, metabolite of Cissampelos sympodialis has acute anti-inflammatory activity. For this purpose, we used the model of paw edema induced by phlogistic agents, histological analysis, anaphylactic shock reaction, scratching behavior and antinociceptive activity tests such as writhing and hot plate. The pretreatment of animals with milonina was able to inhibit significantly (p <0.05) paw edema induced by carrageenan in the period between one and two hours while the challenge with compound 48/80, the milonia was capable of inhibiting (p <0.05) the edema at two times 30 and 60 min. The milonina at 2mg / kg was able to protect 75% of animals from death induced by compound 48/80 in anaphylactic shock test. The morphological analysis of the skin of animals subjected to the itch behavior induced by compound 48/80 showed preservation of epithelial structures. In addition, milonina was able to decrease significantly (p <0.05), nociception induced by acetic acid and hot plate a pattern of the inhibition of inflammatory pain. Thus, these data suggest that milonina has acute anti-inflammatory activity via inhibition of mast cell action.